Video Analysis for Skill and Technique Assessment - Hume, P.; Morrison, J.
Video analysis aims to provide feedback to coaches and competitors with a goal of increasing the desired performance. The athlete`s technique can be studied usually at slow speed or frame by frame. Qualitative (subjective assessment - non numerical evaluation) and quantitative (measurement based - provides kinematics and kinetics) feedback can provide a description of movement in detail. Two-dimensional or three-dimensional analysis can be chosen depending on the type of movement patterns. The aim of this chapter is to outline how to obtain good video images suitable for analysis and several keys points for interpreting the movement patterns.